Trichoderma-Based Biocontrol Strategies Against Fusarium Wilt: A Bibliometric Analysis and literature Review - Anton Meilus Putra (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2026)
Fusarium wilt is one of the most destructive soil-borne diseases threatening global food security. For decades, its control has relied heavily on synthetic chemical fungicides; however, their extensive use has led to pathogen resistance, environmental degradation, and risks to human health. Trichoderma has been widely investigated as a potential biological control agent due to its diverse mechanisms of action. This study aims to map the global research landscape on the application of Trichoderma in controlling Fusarium wilt through bibliometric analysis and literature review. Data were retrieved from the Scopus database (2015–2025) using selected keywords and analyzed with VOSviewer and Biblioshiny to identify publication trends, author collaborations, institutions, countries, and keyword clusters. The results indicate a marked increase in publications since 2020, with major contributions originating from India, China, and Egypt. The evolution of keywords indicates a shift in research focus from basic mechanistic studies to practical field applications. The literature review confirms the effectiveness of Trichoderma in suppressing disease and enhancing the productivity of agricultural commodities, although challenges persist in formulation, variability, and regulatory frameworks. These findings provide an important scientific basis for guiding future research, strengthening international collaboration, and supporting sustainable agricultural strategies that utilize biological control agents.